Effect of Pilates Exercises on Stable and Unstable Surfaces on the Functional Balance and Core Stability of Older Women - Azita Jamalzad Fallah; Ali Shamsi Majelan; Parisa Sedaghati (Shahid Beheshti University of Medical Sciences, 2021)
Background and Aims Balance disorders and frequent falling are the important problems in the elderly, which is directly related to changes in their body structure and function. Many studies have been conducted to find new and safe ways to improve the balance of the elderly. This study aims to compare the effects of Pilates exercises on stable and unstable surfaces on the functional balance and core stability of older women.Methods In this quasi-experimental study, the study population includes all older women living in private nursing homes, in Rasht, Iran. Of these, 36 women aged 60-75 years were selected by a convenience sampling method and randomly assigned to three groups of control, Pilates on stable surface, and Pilates on unstable surface. The variables were assessed using the Fullerton advanced balance test, timed up & go test, and the McGill core endurance test. Experimental groups performed Pilates exercises for 8 weeks, while the control group performed their routine daily activities. Data were analyzed by one-way analysis of variance, t-test and Bonferroni's post hoc test. The significance level was set at 0.05.Results There was a significant difference between the experimental and control groups; however, there was no significant difference between the experimental groups performed exercises on stable and unstable levels (P>0.05) Conclusion It is recommended to use Pilates exercises on stable or unstable surfaces for older women, especially residents of nursing homes with low mobility, to achieve their personal autonomy.